Relationship between dyslexia awareness and stigma among nursing students in Saudi Arabia: A cross-sectional study - Duaa Hafez; Raghad Shafie; Renad Alasiri; Renad Bamasag; Zikra Batwa; Alaa Mahsoon; Loujain Sharif; Nofaa Alasmee (Belitung Raya Foundation, Indonesia, 2023)
Background: Dyslexia—a learning disorder characterized by difficulty in word-level reading skills—can negatively impact nursing students’ practice, which can, in turn, affect patient safety. Individuals with dyslexia are often stigmatized. There is a need to explore dyslexia awareness among nursing students and its relationship with stigma in Saudi Arabia. Objective: This study aimed to assess the dyslexia awareness levels among nursing students and its relation to stigma. Methods: A quantitative cross-sectional study was conducted on 154 nursing students at King Abdulaziz University, Saudi Arabia. Data were collected by asking the students to virtually complete the Knowledge and Beliefs about Developmental Dyslexia Scale (KBDDS) and the Consciousness Questionnaire-Learning Disabilities (SCQ-LD) from February to March 2021. Data were analyzed using chi-square tests to test significance and Cramer’s V to determine the strength of the relationships among the categorical variables. Results: The overall dyslexia awareness level was moderate. Most participants believed that people had negative assumptions about individuals with dyslexia and that they judged and treated them differently. A moderately strong positive association was revealed between knowledge of the stigma surrounding dyslexia and knowledge of dyslexia itself (p <0.001). Conclusions: Increased dyslexia awareness is correlated with greater anticipation that dyslexic individuals will be stigmatized. Therefore, dyslexia awareness should be raised among nursing students. Students or nurses with dyslexia should also be encouraged to learn appropriate coping strategies to ensure patient safety.